STUDENTS' MOTIVATION BECOMING ENGLISH TEACHER STUDENTS AT STKIP MUHAMMADIYAH MUARA BUNGO - Trisnawati, Winda; Oktavia, Diana; Anggelia, Rensi Yu (Universitas Muhammadiyah Muara Bungo, 2021)
This research was conducted to find out the students' motivation and factor becoming English department students at STKIP Muhammadiyah Muara Bungo. This research was completed using the qualitative method, case study approach. The data of this research was collected through interview and documentation. This research was conducted in English education department of STKIP Muhammadiyah Muara, involving 20 students as the respondents. Those students were studying in different semesters, semester 2, 4, and 6. The results of this research were obtained, the motivation of students to become English education students at STKIP Muhammadiyah Muara Bungo is, there are indicators or supporting elements that bring a big role in the success of individuals in learning, especially in learning English. By learning English makes, respondents have a feeling of need for satisfaction, self-esteem needs, and self-actualization. Factor motivation of students to become Students of English education at STKIP Muhammadiyah Muara Bungo above is the encouragement of intrinsic and extrinsic factors in learning English. From the above also researcher concluded that students learning English is greater controlled by intrinsic factors than extrinsic.